2016
DOI: 10.1186/s13287-016-0419-8
|View full text |Cite
|
Sign up to set email alerts
|

Responses to altered oxygen tension are distinct between human stem cells of high and low chondrogenic capacity

Abstract: BackgroundLowering oxygen from atmospheric level (hyperoxia) to the physiological level (physioxia) of articular cartilage promotes mesenchymal stem cell (MSC) chondrogenesis. However, the literature is equivocal regarding the benefits of physioxic culture on preventing hypertrophy of MSC-derived chondrocytes. Articular cartilage progenitors (ACPs) undergo chondrogenic differentiation with reduced hypertrophy marker expression in hyperoxia but have not been studied in physioxia. This study sought to delineate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 53 publications
11
47
0
Order By: Relevance
“…Another positive effect of hypoxia was the significant reduction in ALP activity in MSC and co-culture constructs, thereby further increasing the quality of the cartilage tissue formed by MSCs. A downregulation of hypertrophic markers and terminal differentiation of MSCs by hypoxia has also been documented in previous studies [ 52 , 55 , 56 , 59 , 60 ]. In the present study, furthermore, PRG4 gene expression was significantly upregulated in ACPCs under hypoxia on day 14 and day 28; however, it was significantly downregulated in co-culture constructs under hypoxia on both days.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Another positive effect of hypoxia was the significant reduction in ALP activity in MSC and co-culture constructs, thereby further increasing the quality of the cartilage tissue formed by MSCs. A downregulation of hypertrophic markers and terminal differentiation of MSCs by hypoxia has also been documented in previous studies [ 52 , 55 , 56 , 59 , 60 ]. In the present study, furthermore, PRG4 gene expression was significantly upregulated in ACPCs under hypoxia on day 14 and day 28; however, it was significantly downregulated in co-culture constructs under hypoxia on both days.…”
Section: Discussionsupporting
confidence: 78%
“…It seemed as if hypoxia enabled MSCs to suppress PRG4 expression of ACPCs in co-cultures, which might not be a desirable effect, but is still worthwhile investigating in further studies. With regard to ACPCs, only a few studies have investigated chondrogenic differentiation under hypoxia before [ 25 , 59 ]. When cultured in self-organized constructs on fibronectin-coated membranes, human ACPCs, in contrast to articular chondrocytes, showed only minor responses to reduced oxygen tension (5 %) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of a well characterized allogenic cell bank are clear given the range of GAG and collagen contents due to donor variability. In chondrocyte progenitor experiments, this has been further focused in on showing clonal variability [40] . Interestingly, while there was a wide range of extracellular matrix component concentrations detected, the distribution in mechanical properties was actually relatively narrow.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently observed rapid development of three-dimensional (3D) cancer models re-emphasizes the need to mimic the tumor microenvironment, including the oxygen tension, which has been considered as the limiting nutrient for 3D cell cultures [ 43 , 44 ]. Another important research trend on physioxia observed lately is human fibroblast [ 45 ] and steam cells biology [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%